Hidden constraints to digital financial inclusion: the oral-literate divide. Issue 8 (17th November 2019) - Matthews, Brett Hudson
ABSTRACT: The vision that digital finance can achieve universal financial inclusion is premised on the rarely questioned assumption that the world is rapidly moving towards universal literacy and numeracy. In fact, text and arithmetic notation shape the relationship between formal finance and about a billion of the world's poorest adults. This "oral" population, stranded outside the reach of formal employment, have neither the capabilities nor the incentives to engage in digital finance as it is currently being offered. Empirical observation of the actual capabilities and incentives of oral adults can offer transformative solutions for mobile wallet providers, NGO projects, designers and governments.